Terrence Malick and the Thought of Film - Rybin, Steven (Lexington Books, 2011)
As the director of Badlands, Days of Heaven, The Thin Red Line, and The New World, Terrence Malick has created a remarkable body of work that enables imaginative acts of philosophical interpretation. Steven Rybin's Terrence Malick and the Thought of Film looks closely at the dialogue between Malick's films and our powers of thinking, showing how his work casts the philosophy of thinkers such as Stanley Cavell, Martin Heidegger, Walter Benjamin, André Bazin, Edgar Morin, and Immanuel Kant in new cinematic light. With a special focus on how the voices of Malick's characters move us to thought, Terrence Malick and the Thought of Film offers new readings of his films and places Malick's work in the context of recent debates in the interdisciplinary field of film and philosophy. Rybin also provides a postscript on Malick's recently-released fifth film, The Tree of Life.